The Effect Of Product Innovation And Competitive Advantage On Sales(Case Study of Syarah Bakery Shop, Bengkulu City) - Merta Kusuma; Ika Siti Nur Dharyanti (Penerbit Jurnal Indonesia, 2023)
This study aims to determine